Beyond Classical Fiqh: The Disharmony of Applying ‘Iddah to Women Divorced through Qabla Dukhul Talaq in Brunei Darussalam - Ridho Purnomo; Azam Mabrury Al-Kautsar; Ahmad Qomaruzzaman (STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
Contemporary reforms of Islamic family law in Muslim countries have often produced legal provisions that differ from classical fiqh doctrines. One notable example can be found in Brunei Darussalam, which requires a waiting period (‘iddah) for women divorced before the consummation of marriage (qabla dukh?l divorce), as stipulated in Article 13(3) of the Islamic Family Law (Emergency Order) 1999. This provision departs from the dominant Syafi‘i juristic position, which generally exempts women divorced before consummation from the obligation of ‘iddah. Although previous studies have examined Islamic family law reform in Brunei Darussalam, limited attention has been given to the legal rationale and normative foundations underlying the application of ‘iddah in cases of qabla dukh?l divorce. This study aims to analyze the legal basis, implementation, and normative reasoning behind the enforcement of ‘iddah for women divorced prior to consummation in Brunei Darussalam. Employing a normative juridical method, the study utilizes both a conceptual approach and a statutory approach. Primary sources include the Qur’an and the Islamic Family Law (Emergency Order) 1999, while secondary sources consist of fiqh literature, scholarly books, academic journal articles, and expert opinions. The findings reveal that the application of ‘iddah in cases of qabla dukh?l divorce is grounded in considerations of ma?la?ah (public interest), local custom (‘urf), and the precautionary legal principle of al-i?tiy??. Furthermore, the legislation does not clearly distinguish between dukh?l ?aq?q? (actual consummation) and dukh?l ?ukm? (constructive consummation), thereby allowing broader legal interpretation in its implementation. This study contributes to the scholarship on Islamic family law reform by demonstrating how a modern Muslim state reconstructs classical fiqh doctrines through the integration of ma?la?ah, local customs, and contemporary regulatory needs. [Reformasi hukum keluarga Islam di negara-negara Muslim kontemporer sering kali menghasilkan ketentuan yang berbeda dari doktrin fikih klasik. Salah satu kasus yang menarik ditemukan di Brunei Darussalam yang mewajibkan masa idah bagi perempuan yang bercerai sebelum terjadinya hubungan suami istri (talak qabla dukh?l), sebagaimana diatur dalam Pasal 13 ayat (3) Perintah Darurat (Undang-Undang Hukum Keluarga Islam) Tahun 1999. Ketentuan ini berbeda dengan pandangan dominan fikih mazhab Syafi‘iyyah yang tidak mewajibkan idah bagi perempuan yang dicerai sebelum terjadinya persetubuhan. Meskipun berbagai kajian telah membahas reformasi hukum keluarga Islam di Brunei Darussalam, belum banyak penelitian yang secara khusus menganalisis dasar yuridis dan rasionalitas hukum di balik pemberlakuan idah pada kasus qabla dukh?l. Penelitian ini bertujuan menganalisis dasar hukum, implementasi, dan argumentasi normatif yang melandasi pemberlakuan idah bagi perempuan yang ditalak qabla dukh?l di Brunei Darussalam. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan konseptual (conceptual approach) dan pendekatan perundang-undangan (statute approach). Data primer diperoleh dari Al-Qur’an dan Perintah Darurat (Undang-Undang Hukum Keluarga Islam) Tahun 1999, sedangkan data sekunder berasal dari literatur fikih, buku, jurnal ilmiah, dan pendapat para ahli. Hasil penelitian menunjukkan bahwa pemberlakuan idah dalam kasus qabla dukh?l di Brunei Darussalam didasarkan pada pertimbangan ma?la?ah, adat setempat (‘urf), serta prinsip kehati-hatian hukum (al-i?tiy??). Selain itu, ketentuan tersebut tidak memberikan penjelasan yang tegas mengenai batasan antara dukh?l ?aq?q? dan dukh?l ?ukm?, sehingga membuka ruang interpretasi yang lebih luas dalam penerapannya. Penelitian ini berkontribusi pada pengembangan kajian reformasi hukum keluarga Islam dengan menunjukkan bagaimana negara dapat merekonstruksi doktrin fikih klasik melalui integrasi antara prinsip ma?la?ah, adat lokal, dan kebutuhan regulasi hukum modern.]